ORGANIZATIONAL COMMITMENT OF HEALTHCARE EMPLOYEES IN A PRIVATE SECTOR - Dugalic, Stefan; Santric- Milicevic, Milena; Stanisavljevic, Dejana; Gutic Vukobrat , Bojana; Gojnic, Miroslava; Macura, Maja; Bozic, Dragana; Stanisavljevic, Tamara; Petronijevic, Milos; Vrzic- Petronijevic, Svetlana; Petronijevic, Milica; Todorovic, Jovana (Medical Research, 2022)
Introduction: Organizational commitment is defined as ‘psychological relationship of an individual with an organization’. The aims of this study were to analyze organizational affective and normative commitment of young healthcare providers, factors that determine their perception of organizational support, as well as to identify possibilities to promote employee dedication to the healthcare organization they worked for.Method: The research was conducted as a cross-sectional study in a private healthcare institution ‘Fizio Vracar’ in Belgrade. Meyer-Allen questionnaire (with 24 questions) was distributed during the third week of May 2018, and 30 physical therapists of both sexes and with median age 29.9 completed it, voluntarily and anonymously.Results: The hypothesis was proven: organizational normative commitment declined with the increase of organizational support (r=-0.526; p